Endurance determination of different buckwheat cultivars to aluminum by FTIR spectrum - ZHANG Ya-nan; WANG Ying; CHEN Qi; HUANG Shu-shi; LI Kun-zhi (浙江大学学报. 农业与生命科学版, 2010)
The Al-tolerance of two different varieties (Chun-Hong 1, Chun-Hong 4) of buckwheat was analyzed and identified by Fourier transform infrared (FTIR) spectroscopy and conventional experimental method of root elongation. By comparison of root, stem and leaf characteristics of the infrared spectra peaks 3 353, 2 923, 1 734, 1 643, 1 453, 1 367, 1 250 and 1 055 cm-1 between the two varieties under the different Al concentrations, most of the characteristic peaks in Chun-Hong 1 were higher than that in Chun-Hong 4. Characteristics of the FTIR peak for the root, stem and leaf in Chun-Hong 1 and Chun- Hong 4 were increased with increase of Al concentrations. FTIR peak of Chun-Hong 1 reached the maximum when the Al concentration increased to 50 μmol·L-1, while that of Chun-Hong 4 reached the maximum at the Al concentration of 20 μmol·L-1. Besides, the results showed that the FTIR spectra of Chun-Hong 4 varied much greater in roots, stems and leaves than aluminum-resistant cultivar Chun- Hong 1 under different Al concentrations, implying that Chun-Hong 4 metabolism was evidently affected by Al. The results of root elongation experiment showed that the root growth of Chun-Hong 1 was promoted and the amount of root elongation reached the maximum of 140% compared with the control, while that of Chun-Hong 4 was greatly inhibited and its elongation was only 80% of the control with the treatment of 20 μmol·L-1 Al. These findings demonstrate that Al endurance of Chun-Hong 1 is stronger than Chun-Hong 4, and FTIR spectra can be developed as a new, rapid and accurate method for the endurance identification of different buckwheat cultivars to Al.